An Overview of SARS-CoV-2 and Animal Infection - Mahdy, Mohamed A. A.; Younis, Waleed; Ewaida, Zamzam (Frontiers in Veterinary Science, 2020)
A novel coronavirus has been reported as the causative pathogen of the Coronavirus disease 2019 (COVID-19) outbreak in Wuhan city, China in December 2019. Due to the rapid spread of the virus worldwide, it has been announced as a pandemic by the World Health Organization (WHO). Hospitalized patients in Wuhan were associated with the Huanan seafood wholesale market where live animals, such as poultry, bats, snakes, frogs, rabbits, marmots, and hedgehogs are sold in that market which suggests possible zoonotic infection. It was suggested that bat is the natural host of SARS-CoV-2, but the intermediate host is still unclear. It is essential to identify the potential intermediate host to interrupt the transmission chain of the virus. Pangolin is a highly suspected candidate as an intermediate host for SARS-CoV-2. Recently, SARS-CoV-2 infection has been reported in cats, dogs, tigers, and lions. More recently SARS-CoV-2 infection affected minks severely and zoonotic transfer with a variant SARS-CoV-2 strain evidenced in Denmark, Netherlands, USA, and Spain suggesting animal-to-human and animal-to-animal transmission within mink farms. Furthermore, experimental studies documented the susceptibility of different animal species to SARS-CoV-2, such as mice, golden hamsters, cats, ferrets, non-human primates, and treeshrews. It is also essential to know the possibility of infection for other animal species. This short review aims to provide an overview on the relation between severe acute respiratory syndrome coronavirus‐2 (SARS‐CoV‐2) infection and animals.